2012
DOI: 10.5098/hmt.v3.1.3003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Microlayer Formation and Heat Transfer in Mini/Microchannel Boiling Systems: A Review

Abstract: This paper reviews recent research on microlayer formed by confined vapor bubbles during boiling in mini/microchannels. Experimental measurements, simulations and theoretical studies are described and compared. As a reference to clarify the mechanism for the formation of a microlayer, Taylor flow (i.e. elongated bubble flow in mini/micro circular tubes under adiabatic conditions and at Re << 1) and elongated bubble flow at high velocity, with consideration of the influence of inertia, are also reviewed. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
4
0
2
Order By: Relevance
“…Utaka and colleagues have more recently investigated the initial microlayer formation for elongated bubbles within micro-channels, and studied the effect of different physical conditions on the microlayer thickness (Utaka et al, 2009, Zhang et al, 2010, Zhang and Utaka, 2012, Zhang and Utaka, 2015. In micro-channels, it is suggested that microlayer thicknesses increase linearly with increasing viscosity and decreasing surface tension.…”
Section: Microlayer Hydrodynamic Predictionmentioning
confidence: 99%
“…Utaka and colleagues have more recently investigated the initial microlayer formation for elongated bubbles within micro-channels, and studied the effect of different physical conditions on the microlayer thickness (Utaka et al, 2009, Zhang et al, 2010, Zhang and Utaka, 2012, Zhang and Utaka, 2015. In micro-channels, it is suggested that microlayer thicknesses increase linearly with increasing viscosity and decreasing surface tension.…”
Section: Microlayer Hydrodynamic Predictionmentioning
confidence: 99%
“…In their study, the film thickness was estimated based on the transient variation of wall temperature, by assuming that the change in temperature is due to the heat taken by the thin-film to evaporate completely. A recent review by Zhang and Utaka [25] provides valuable insight into the research conducted on two aspects of thin-film, namely: the thickness of thin-film and its evaporation characteristics. However, this review Recently, Rao et al [27] experimentally studied the effect of imposing a longitudinal thermal gradient on an isolated liquidvapour two-phase system in a capillary tube.…”
Section: Introductionmentioning
confidence: 99%
“…As the steady propagation speed of a bubble increases, the inertial effects cannot be neglected in the problem. The inertial term has to be taken into account, and we must employ the steady Navier-Stokes equation instead of the Stokes equation to describe the problem [4]. Aussillous and Quere [3] also investigated the inertia effect using lowviscosity liquids and found that above a threshold of Ca, the microlayer is thicker than the correlation derived from the Stokes equation.…”
Section: Introductionmentioning
confidence: 99%
“…This requires using the full Navier-Stokes equations rather than the Stokes equations or steady Navier-Stokes equations that neglect local acceleration. However, there are not sufficient published studies on microlayer formation under accelerated motion [4].…”
Section: Introductionmentioning
confidence: 99%